The Algerian Economy Revisited: Reviewing Salient Trends - Aghrout, Ahmed; Meliani, Hakim (جامعة المسيلة, 2009)
It is now an established fact that the Algerian economy has not performed as it should be. Significant investment efforts have been made thanks to the oil revenues. Yet the economy has not produced the increases in output that might be expected. This unsatisfactory economic performance is mainly due to the predominance of inefficient state-owned enterprises, a climate of regulations that are unhelpful to business and the market economy, and a lack of vital enthusiasm needed to reform the financial sector. صار جليا الآن أن الاقتصاد الجزائري لم يأت بما كان منتظرا منه، فرغم كون عائدات النفط ساهمت في توليد جهود استثمارية كبيرة، إلا أن الاقتصاد لم يسفر عن الزيادات الإنتاجية الحقيقة المتوقعة. يرجع هذا الأداء الاقتصادي غير المرضي أساسا إلى عدم كفاءة الشركات المملوكة للدولة، وعدم ملاءمة مناخ الأنظمة لقطاع الأعمال واقتصاد السوق، وعدم وجود الحماس من الحيوية اللازمة لإصلاح القطاع المالي.